Hubungan Tingkat Pengetahuan Gizi dan Tingkat Kecukupan Asupan Zat Besi dengan Status Anemia Ibu Hamil di Puskesmas Brebes - Aditya Hanif Permana; Yuniarti Dewi R; Rifatul Masrikhiyah; Diah Ratnasari (Lembaga Pengembangan Kinerja Dosen, 2026)
Iron deficiency anemia remains a major public health problem among pregnant women in Indonesia, with a national prevalence of 37.1% and higher rates in regions such as Brebes Regency. Adequate nutritional knowledge and sufficient iron intake are expected to prevent decreases in hemoglobin (Hb) levels during the third trimester. This study aimed to analyze the relationship between nutritional knowledge, iron intake adequacy, and Hb levels among third-trimester pregnant women at Puskesmas Brebes. An analytic observational study with a cross-sectional design was conducted on 62 respondents using total sampling. Data were collected through a nutritional knowledge questionnaire, a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) to assess iron intake based on the Recommended Dietary Allowance of 27 mg/day, and Hb measurement using a digital device. The prevalence of anemia was 32.3%, with a mean Hb level of 11.25 ± 1.74 g/dL. Most respondents had high nutritional knowledge (72.6%), but 79.0% had inadequate iron intake. Chi-Square analysis showed no significant relationship between nutritional knowledge and Hb levels (p=0.109) or between iron intake adequacy and Hb levels (p=0.426). Other factors, including iron absorption inhibitors, compliance with iron supplementation, nutritional status, and limited sample size, may have influenced the results.